Reversed-phase HPLC Seperation of Quinine and its Diastereoisomer Quinidine in Pharmaceutical Tablets - Fegas, R.; Adoui, A.; Siouffi, A.M. (Asian Journal of Chemistry, 2010)
In this paper, the effects of mobile phase composition on the retention time and peak shape of quinine and quinidine in tablets are described. The method is reproducible and sensitive and suitable for routine use.